2014
DOI: 10.1158/0008-5472.can-13-3182
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Inhibition by Sustained Overproduction of IL6 Contributes to Arsenic Carcinogenesis

Abstract: Chronic inflammation has been implicated as an etiological factor in cancer, whereas autophagy may help preserve cancer cell survival but exert anti-inflammatory effects. How these phenomena interact during carcinogenesis remains unclear. We explored this question in a human bronchial epithelial cell-based model of lung carcinogenesis that is mediated by sub-chronic exposure to arsenic. We found that sustained overexpression of the pro-inflammatory interleukin IL-6 promoted arsenic-induced cell transformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
64
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 42 publications
1
64
0
Order By: Relevance
“…Recently, we further uncovered the involvement of an STAT3-mediated autophagy and inflammation responses in this process. 2 Chronic sterile inflammation caused by continuous carcinogen exposure has been linked to various steps of tumorigenesis. A pathogenic effect of pulmonary inflammation has been shown in several murine models of lung cancer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we further uncovered the involvement of an STAT3-mediated autophagy and inflammation responses in this process. 2 Chronic sterile inflammation caused by continuous carcinogen exposure has been linked to various steps of tumorigenesis. A pathogenic effect of pulmonary inflammation has been shown in several murine models of lung cancer.…”
mentioning
confidence: 99%
“…2 The level of IL6 is increased upon prolonged arsenic exposure which inhibits autophagy activation and thus enhances arsenic-induced cell transformation. Our in both epithelial and immune cells through autocrine or paracrine mechanisms.…”
mentioning
confidence: 99%
“…These observations suggest that any pro-inflammatory stimulus or agent that gains entry to the body through different routes could induce the same negative effect on human cognitive functions. In this sense, several reports have shown that acute or chronic exposure to iAs or its methylated metabolites lead to inflammatory responses activation in diverse cell types [15][16][17]; therefore, exposure to arsenicals may increase the risk for cognitive impairment through the induction of a sustained inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…These are combined with an exaggerated and often inappropriate inflammatory response. For example, the research of several investigators has shown that prenatal arsenic exposure produces altered pro-inflammatory signaling [7,8], including the overproduction of pro-inflammatory cytokines such as interleukin-6 (IL-6) [9]. Inappropriate immune production of inflammatory mediators facilitates the activation of redox pathways [10], which contributes to tissue pathology and potentially to later-life cancer.…”
Section: Arsenicmentioning
confidence: 99%